2019
DOI: 10.5708/ejmh.14.2019.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Compassion-Oriented Mindfulness-Based Program and Health Professionals : A Single-Centered Pilot Study on Burnout

Abstract: This pre-post, single-centered study evaluates the effects of a compassion-oriented mindfulnessbased intervention on health professionals' quality of life. The intervention was conducted in an Italian general hospital in the province of Milan. Between 2014 and 2015, thirty-four health professionals operating in the territorial psychiatric services followed an 18-week Compassion-Oriented Mindfulness-based Program. The program involved the practice of mindfulness meditation combined with a psycho-educational tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Bagaric and Markanovic (2020) [ 22 ] found a significant decrease in burnout symptoms reported by participants post-intervention; however, these results were not maintained at two month follow up. Marconi et al (2019) [ 18 ] examined an intervention consisting of biweekly classes consisting of compassion-oriented mindfulness-based exercises over the course of 18-weeks among 34 psychiatric health professionals recruited from the G. Salvini Hospital in Milan. The authors found that, post- intervention, there were statistically significant reductions in emotional exhaustion on the Maslach Burnout Inventory (MBI).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bagaric and Markanovic (2020) [ 22 ] found a significant decrease in burnout symptoms reported by participants post-intervention; however, these results were not maintained at two month follow up. Marconi et al (2019) [ 18 ] examined an intervention consisting of biweekly classes consisting of compassion-oriented mindfulness-based exercises over the course of 18-weeks among 34 psychiatric health professionals recruited from the G. Salvini Hospital in Milan. The authors found that, post- intervention, there were statistically significant reductions in emotional exhaustion on the Maslach Burnout Inventory (MBI).…”
Section: Resultsmentioning
confidence: 99%
“…Márquez and colleagues (2021) [ 20 ] noted that, for a population of national police officers, mean scores for observing and not-reacting on the Five Facets of Mindfulness Questionnaire (FFMQ) improved from pre- to post-intervention. There was also an increase in the observing and nonreactivity of inner experiences subscales on the FFMQ for psychiatric health professionals (Marconi et al, 2019) [ 18 ]. Similarly, Bagaric and Markanovic (2020) [ 22 ] found significant changes on the FFMQ observation, non-judgement, and non-response subscales post-intervention; however, changes were not observed in the description and awareness subscales among prison employees.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations